ADVERBIA PENANDA ASPEK DALAM NOVEL NEGERI 5 MENARA KARYA AHMAD FUADI - Marliana, Mila Ana; Agustina, Agustina; Ngusman, Ngusman (Jurnal Bahasa dan Sastra, 2018)
This study was conducted to describe the use of adverbs in Novel Negeri 5 Menara Work Ahmad Fuadi. Â This research is a qualitative research using descriptive method. The data in this study are words that include the use of adverbs in Novel Negeri 5 Menara Work Ahmad Fuadi. The data are collected in the following way, (1) reading and comprehending the entire contents of novel Negeri 5 Menara Work Ahmad Fuadi; (2) marking the parts in the form of words that the research aims; and (3) to inventory the data contained in the novel text. The examination of data validation in this study uses a detailed description technique. After data is collected, then analyzed by the following steps, (1) identifying the data, (2) classifying the data, (3) interpreting the data, and (4) summing up the data. The conclusion of this research is the use of adverbs in Novel Negeri 5 Menara Work Ahmad Fuadi is found. The statement is evidenced by the phrase in the Novel Negeri 5 Menara Work Ahmad Fuadi shows the appearance of adverbs of aspect markers. The research finds in the Novel Negeri 5 Menara Work Ahmad Fuadi adverbs aspect marker as many as 69 data for the use of adverbs as aspect markers.Â Keywords: adverbs, aspect markers, novels